Gestión de tesorería y su impacto en la eficiencia, eficacia y economía del departamento de renta del gad municipal del cantón el empalme, año 2023. - Salas Torres, Selena Tatiana (2025)
This research addressed the topic of treasury management, which stands as a fundamental tool for ensuring efficient management of public funds. Therefore, the purpose of this research was to evaluate the impact of treasury management on the efficiency, effectiveness, and economy of the Revenue Department of the Municipal GAD of the El Empalme Canton in 2023. The research was of a mixed nature with a qualitative- quantitative approach. Explanatory, descriptive, and exploratory research methods were applied to obtain, analyze, and develop the study. Inductive, deductive, historical-logical, and descriptive research methods were also applied; these allowed for identifying the causes and effects of the problem, as well as obtaining general conclusions from the research. The sample population included the heads of the Revenue Department and a total of nine people, including internal staff. Since this was a finite population, the sample was census-based, with interviews and surveys conducted respectively. The results show that treasury management is enhanced by the implementation of the Integrated Municipal Information System (SIIM), financial planning, and cooperation between departments. Eighty percent of respondents believe that financial planning and oversight contribute to the achievement of institutional goals. Therefore, it is concluded that the efficiency of the Revenue Department's treasury management depends on the constant updating of its procedures and the strengthening of its human capital.